SUPPLEMENTATION OF MAGGOT BLACK SOLDIER FLY (BSF) MEAL IN COMMERCIAL RATIONS FOR IMPROVING BROILER PERFORMANCE - I G. A., Mahardika; Umiarti, A. T.; Suarta, G. (Jurnal Peternakan Tropika, 2024)
The purpose of this research is to find out if broiler performance can be improved by adding Black Soldier Fly (BSF) maggot meal to their feeds. Over the course of four weeks in April and May of 2023, researchers in Tengkudak Village, Penebel District, Tabanan Regency, Bali, used a totally randomized design with four treatments and four  replications, with four broilers each replication. The treatment included three different rations supplemented with different amounts of maggot meal: P0, which did not include any, P1, which contained 3% maggot meal, P2, which contained 6% maggot meal, and P3, which contained 9% maggot meal. Gain in body weight, feed intake, feed conversion, end weight, and index performance were the variables tracked. Treatment P0 had considerably lower final weight, body weight increase, feed intake, feed conversion, and performance index compared to treatments P1, P2, and P3, according to this study's findings (P<0.05). This study's findings suggest that commercial rations supplemented with up to 9 percent maggot flour may improve feed conversion efficiency, boost ration intake and performance index, and enhance body weight and final weight.